SYSTEM GOVERNANCE STUDY INFORMATION ON PT MEGA AUTO CENTRAL FINANCE MAKASSAR - Asim (PUSAT KEWIRAUSAHAAN UNIVERSITAS BALIKPAPAN, 2023)
Governance studies system information on PT. Mega auto central finance (MCF). Objective research: (1). Measure level collection capabilities of PT. MCF. (2). Evaluate governance information system services at PT. MCF. PT. MCF is a company financing growing motorcycles rapidly, founded on September 24, 2007, with amount employee moment This is about 8000 people and the sample consists of 40 employees of 38 MCF employees, 1 Collection coordinator and marketing head. The study uses the framework COBIT 5.0 work and focuses on evaluating, directing, and monitoring (EDM) domains. There are several subdomains that help the research process i.e., EDM01 (ensure setup and maintenance governance framework), EDM02 (make sure delivery benefits), EDM03 (make sure optimization risk), EDM04 (make sure optimization source power), EDM05 (make sure stakeholder transparency). Based on the results of governance evaluation system information using the known COBIT 5 framework capability level collection i.e., is on a scale of 3 (established process), the process has been implemented using a specific process that has been set, which is capable achieve the expected outcome.